Desafios e possibilidades da ludicidade no ambiente hospitalar: análise da produção científica sobre pedagogia hospitalar em Programas de Pós-Graduação - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá)
It is possible to recognize that children, in non-school spaces such as the hospital environment, can perform various activities regardless of their illness, such as educational actions through the use of playfulness. From the knowledge production modality, this study aimed to know the challenges and possibilities that education professionals face to carry out recreational activities in the hospital environment. This is an exploratory and descriptive study using a qualitative approach. The methodological procedures followed the path of bibliographic research in the context of knowledge production, using content analysis as a technique for treating the results. To this end, a bibliographic survey of theses and dissertations defended in Brazil was carried out, from 2008 to 2019, in the Brazilian Digital Library of Theses and Dissertations and in the database of the Coordination for the Improvement of Higher Education Personnel. As a result, for the conformation of the bibliographic corpus for the study, 32 studies were selected, being 8 theses and 24 dissertations. From the content analysis, 3 thematic subcategories emerged at first and later 6 subthemes inferred in the study and interpretation of theses and dissertations. The results indicated that the theme of Hospital Pedagogy from a ludic perspective is rarely addressed in the scientific production published in theses and dissertations. There was a disparity in the production of knowledge regarding geographic regions, with the Southeast region predominating with the largest number of theses and dissertations. The playful activities and their repercussions pointed to playfulness not only as fun, but in the development of the child/adolescent's potential in the hospital environment. The challenges for playfulness in the hospital environment revealed a correlation between the structural obstacles and the technical mastery of skills, abilities and knowledge that are essential for carrying out playful-therapeutic activities. And the possibilities of overcoming the challenges pointed out for the effectiveness of playfulness in the pedagogical practice in the hospital environment emphasize that the different knowledge, on the part of education professionals, must go beyond the technical skills of training, also incorporating their life trajectories, beliefs, and values. Therefore, it is suggested to continue studies with this theme, which favor methodological paths capable of favoring more systematic studies.
Keywords: Pedagogia hospitalar; Ambiente hospitalar - Atividades lúdicas; Ambiente hospitalar - Ludicidade; Educação hospitalar; CNPQ::CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO